HAMBATAN EPISTIMOLOGIS SISWA DALAM MENENTUKAN DOMAIN DAN RANGE FUNGSI KUADRAT DI SEKOLAH MENENGAH ATAS - Rasmania, Rasmania; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to explain the epistimological obstacles of students in determining the Domain and Range quadratic function in the class eleventh SMA Islam Al-Asy 'Arriyah Pontianak academic year 2017/2018. Subjects who participated in this study were four students of class eleventh who had obstacles in solving the problem Domain and Range. The method used in this research is case study. The instrument used test amounted to 12 questions. Based on the results of the tests and interviews by four students, had found some obstacles in determining Domain and Range quadratic function.They have not been able to write and understand the symbol used on the problem. Meanwhile, the subjects have not understood how to determine Domain that has two interval, they also have not been able to explain the proper procedure to seek the Range. The four subjects have not been able to determine the draw graph of quadratic functions procedure.Â Keywords: Epistimological Obstacles, Domains, Ranges, Quadratic Functions